2022
DOI: 10.1101/gad.349039.121
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 regulates TIP60 function during fate transition between two-cell-like and pluripotent states

Abstract: In mammals, the conserved telomere binding protein Rap1 serves a diverse set of nontelomeric functions, including activation of the NF-kB signaling pathway, maintenance of metabolic function in vivo, and transcriptional regulation. Here, we uncover the mechanism by which Rap1 modulates gene expression. Using a separation-of-function allele, we show that Rap1 transcriptional regulation is largely independent of TRF2-mediated binding to telomeres and does not involve direct binding to genomic loci. Instead, Rap1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Unlike Zscan4, other proteins that help maintain telomere length are suppressors rather than activators of ERVs ( Figure 1C ). Telomere-associated proteins, such as Tin2 and Rap1, play a crucial role in silencing MERVL in ESCs ( Barry et al., 2022 ; Yin et al., 2022 ). These findings underscore the significance of telomere length and telomere-associated proteins in the regulation of ERV expression.…”
Section: Transcriptional Regulation Of Ervs In Escs and During Early ...mentioning
confidence: 99%
“…Unlike Zscan4, other proteins that help maintain telomere length are suppressors rather than activators of ERVs ( Figure 1C ). Telomere-associated proteins, such as Tin2 and Rap1, play a crucial role in silencing MERVL in ESCs ( Barry et al., 2022 ; Yin et al., 2022 ). These findings underscore the significance of telomere length and telomere-associated proteins in the regulation of ERV expression.…”
Section: Transcriptional Regulation Of Ervs In Escs and During Early ...mentioning
confidence: 99%
“…Telomere erosion itself is also linked with marked alterations in the epigenetic state [94,[97][98][99]. For example, when telomere protection or telomere erosion are perturbed in mice, genome-wide transcriptional and epigenetic alterations ensue [82,[100][101][102][103][104][105][106][107][108]. Furthermore, during senescence, or upon the distruption of telomere maintenance or Trf1 function, associated changes in the chromatin landscape occur that are linked to the dysregulation of the chromatin modifying complex, Polycomb Repressive Complex 2 (PRC2) and/or to changes in histone or DNA methylation status [81,82,109].…”
Section: Telomeres and Stem Cellsmentioning
confidence: 99%
“…A recent study compared the knockout of several different components in the p400–TIP60 complex in mESCs. The authors found that the individual knockout of TIP60, EPC1, DMAP1, or p400 ( Figure 4 ) produced different effects by up- or downregulating the expression of different subsets of genes [ 118 ]. Thus, the function of p400–TIP60 in depositing H2A.Z during different developmental stages remains unclear.…”
Section: Complexes That Regulate Genome Localization Of H2az During D...mentioning
confidence: 99%